2006
DOI: 10.1136/ard.2005.044073
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac dysfunction in patients with systemic lupus erythematosus and antiphospholipid syndrome

Abstract: Abnormal echocardiographic findings were detected frequently in asymptomatic patients with SLE or PAPS. Although patients with SLE were younger, left ventricular systolic function was more impaired in patients with SLE compared with those with PAPS, whereas left ventricular and right ventricular diastolic function, as reflected by IVRT and E:A ratios, were significantly more impaired in patients with APS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 24 publications
4
32
0
3
Order By: Relevance
“…The association of antiphospholipid syndrome (APS) and DD has been previously documented [27,28]. APS causes myocardial hypoperfusion by small vessel vasculopathy/ microvascular thrombosis [29] which affect myocardial compliance [30].…”
Section: Discussionmentioning
confidence: 99%
“…The association of antiphospholipid syndrome (APS) and DD has been previously documented [27,28]. APS causes myocardial hypoperfusion by small vessel vasculopathy/ microvascular thrombosis [29] which affect myocardial compliance [30].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with both SLE and APS a lower than normal CD4+/ CD8+ ratio in BAL was seen, suggesting subclinical ILD in patients who were asymptomatic regarding respiratory symptoms [164].…”
Section: Bronchoalveolar Lavagementioning
confidence: 99%
“…Paran et al (24) reported abnormal echocardiographic findings in asymptomatic patients with SLE or antiphospholipid syndrome (APS). The SLE patients were younger and LV systolic function was more impaired in patients with SLE than in PAPS; meanwhile, LV and RV diastolic function, as reflected by the E/A ratios, were significantly more impaired in patients with APS.…”
mentioning
confidence: 99%